Significance of thyroid peroxidase antibodies (anti-TPO antibodies) in patients undergoing thyroid function tests - Gautam, Bijaya (Journal of Gandaki Medical College-Nepal, 2024)
Introduction: Thyroid peroxidase (TPO) enzyme is a poorly glycosylated enzyme responsible for the synthesis of the thyroid hormones. TPO antibodies appear where there is tissue destruction in thyroid follicles, thereby making it a good marker for detection of autoimmune thyroid disorders. Thus, this study was conducted to analyze the significance of anti-TPO antibodies in patients undergoing a thyroid function test. Methods: This is a hospital-based cross-sectional study conducted on 235 patients who had undergone thyroid function tests (TFTs) along with anti-TPO. Overnight fasting samples were collected, labeled and stored. The serum level of fT3, fT4, TSH and anti-TPO antibodies were measured using CLIA method from Diasorin Liaison instrumentation. Results: Out of total patients, Male: female ratio of patient was 1:3.35 which showed female preponderance over male. Maximum number of patients belongs to 21 to 30 years age group (87/37.2%). Total 87 patients had thyroid related disorders. Among this, 74 were females, 26 patients had subclinical hypothyroidism (25 were females), 30 had clinical hypothyroidism (26 were females), 4 had subclinical hyperthyroidism (all females) and 27 had clinical hyperthyroidism (19 were females). Positive anti-TPO antibody patients were 73, out of which 59 were female. TSH had significant positive correlation, while T4 and T3 had negative significant correlation with anti-TPO. Conclusions: Assessment of anti-TPO antibodies is valuable while assessing thyroid function tests, as it can help in early diagnosis as well as to establish autoimmune pathogenesis of thyroid disorders.